A qualitative study on the term CAM: is there a need to reinvent the wheel? - Gaboury Isabelle; April Karine; Verhoef Marja (BMC, 2012)
Abstract Background As complementary and alternative medicine (CAM) has developed extensively, uncertainty about the appropriateness of the terms CAM and other CAM-related terms has grown both in the research and practice communities. Various terms and definitions have been proposed over the last three decades, highlighting how little agreement exits in the field. Contextual use of current terms and their respective definitions needs to be discussed and addressed. Methods Relying upon the results of a large international Delphi survey on the adequacy of the term CAM, a focus group of 13 international experts in the field of CAM was held. A forum was also set up for 28 international experts to discuss and refine proposed definitions of both CAM and integrative healthcare (IHC) terms. Audio recordings of the meeting and forum discussion threads were analyzed using interpretive description. Results Multiple terms to describe the therapies, products, and disciplines often referred to as CAM, were considered. Even though participants generally agreed there is a lack of optimal definitions for popular CAM-related umbrella terms and that all terms that have so far been introduced are to some extent problematic, CAM and IHC remained the most popular and accepted terms by far. The names of the specific disciplines were also deemed adequate in certain contexts. Focus group participants clarified the context in which those three terms are appropriate. Existing and emergent definitions of both CAM and integrative healthcare terms were discussed. Conclusions CAM and other related terms could be used more effectively, provided they are used in the proper context. It appears difficult for the time being to reach a consensus on the definition of the term CAM due to the uncertainty of the positioning of CAM in the contemporary healthcare systems. While umbrella terms such as CAM and IHC are useful in the context of research, policy making and education, relevant stakeholders should limit the use of those terms.